A Critical Evaluation of the Special Provisions for Gifted Students: a case study of a student in an Elementary School in Dubai - Sharma, Neha H (2019)
This paper critically evaluates the special provisions made by an International Baccalaureate school in Dubai for a gifted male student in elementary grade. There is very limited research in the field of gifted education within the United Arab Emirates. No prior study about the programs and services offered to the gifted learners in the private schooling sector has been published till date. Although private schools following various curricula in the emirate of Dubai probably make special provisions to identify and cater to the unique needs of the gifted learners, there is no research-based study evaluating these services. Private schools are guided by UAE federal laws regarding inclusive education and are inspected annually by the Knowledge and Human Development Authority. These annual school inspection reports are available in the public domain which comprehensively evaluate the special educational provisions, but do not specifically focus on the gifted programs and services. Lack of research studies and neglect by the local authorities regarding gifted provisions presented the opportunity, vision and rationale for the current qualitative case study. A holistic approach was deemed appropriate to describe and critically analyse the school policy, systems of identification, gifted programs offered and teacher readiness to provide appropriate support to identified gifted learners. This case study attempts to present a rich panorama of the gifted provisions offered in one private school in the UAE. Based on the literature regarding best practices in the field of gifted education, the provisions have been critically evaluated and some suggestions about possible improvements in services alongside few recommendations for future studies have been included in the current study.